2018
DOI: 10.1080/09712119.2018.1490300
|View full text |Cite
|
Sign up to set email alerts
|

Investigation in terms of digestive values, silages quality and nutrient content of the using pomegranate pomace in the ensiling of apple pomace with high moisture contents

Abstract: The purpose of present study was to determine the quality and in vitro digestion parameters in silages of 100% pomegranate pomace (PPS), 100% apple pomace (APS) and 50% pomegranate pomace + 50% apple pomace (PAPS). The digestion parameters of 10% or 20% using of these silages in total mix ration (TMR) of dairy cattle were researched. The dry matter (DM), crude protein, flavonoids, tannins and anthocyanins of pomegranate pomace were higher than those of apple pomace. Fibrous and nonfibrous carbohydrates of pome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
3
5
1
Order By: Relevance
“…The in vitro total gas and digestion values of pomegranate peel in the present study on rumen goat were higher than those of pomegranate pomace in beef cattle reported by Ebrahimi (2012) and Kara et al (2018a). Mirzaei-Aghsaghali et al (2011) found that in vitro ME and OMd gas values of pomegranate peel for rumen fluid of steer beef were 8.85 MJ/kg DM and 59.0%, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The in vitro total gas and digestion values of pomegranate peel in the present study on rumen goat were higher than those of pomegranate pomace in beef cattle reported by Ebrahimi (2012) and Kara et al (2018a). Mirzaei-Aghsaghali et al (2011) found that in vitro ME and OMd gas values of pomegranate peel for rumen fluid of steer beef were 8.85 MJ/kg DM and 59.0%, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The digestible organic matter content of apple pulp has been consistent with the research findings reported by Mirzaei-Aghsaghali et al (2011), while the content of apple pulp silage DOM was higher than the results reported by Abdollahzadeh et al (2010) and Kara et al (2018).…”
Section: In Vitro Gas Production Features Of Silagessupporting
confidence: 90%
“…(2001) and Islam et al (2014) were also reported by. Although the NDF and ADF content detected in apple pulp silage was lower than those determined by Fang et al (2016), it was found higher than the data determined by Kara et al (2018). The amount of NDF (45.3%) and ADF (38.0%) found in this study were similar to the data reported by Abdollahzadeh et al (2010).…”
Section: Chemical Composition Of Feed and Silagessupporting
confidence: 80%
“…Anaerobic fermentation of forage and highfibre feed generates methane that contributes to global warming and waste of feed energy. Recent researches thus have focused on methane emission levels of the forages (Lin et al, 2013;Kara et al, 2018). Different outcomes were reported about methanogenic effects and anti-methanogenic compound contents of different roughage sources (Kara et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%